Feasibility of interim fish production in water-harvesting tanks in rainfed drought-prone areas - Paul, D K (Indian Journal of Fisheries, 2011)
In watershed management project a portion of the cultivable is converted into a small reservoir or water-harvesting tank. To increase the Hofit Aom such farm ponds, intÂ»im fish production was tried along with crop production.